2008
DOI: 10.1029/2007jc004320
|View full text |Cite
|
Sign up to set email alerts
|

Observed and modeled meridional overturning circulation related flow into the Caribbean

Abstract: [1] A major pathway of the Atlantic meridional overturning circulation (MOC) is the warm inflow into the Caribbean Sea. The transport and the contribution of water from the South Atlantic is calculated from observations (ADCP data and hydrography) and compared to the results of the 1 12°F LAME model. The model and the observations show high consistency in the strength of the mean total inflow and its range of variability as well as in the general distribution of water from South Atlantic origin. The measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 23 publications
9
40
2
Order By: Relevance
“…1), connecting the Caribbean Sea with the Atlantic. Recent observations combined with a model study suggest that a total flow of 17-19 Sv passes through the Lesser Antilles into the Caribbean Sea (Kirchner et al, 2008), implying that the western boundary current across the 14.5 • N section must recirculate southward across the section in the east, as occurs in both realizations (Fig. 12a, b).…”
Section: Discussionmentioning
confidence: 81%
“…1), connecting the Caribbean Sea with the Atlantic. Recent observations combined with a model study suggest that a total flow of 17-19 Sv passes through the Lesser Antilles into the Caribbean Sea (Kirchner et al, 2008), implying that the western boundary current across the 14.5 • N section must recirculate southward across the section in the east, as occurs in both realizations (Fig. 12a, b).…”
Section: Discussionmentioning
confidence: 81%
“…The study of Kirchner et al [2008] included a detailed model data comparison, indicating a realistic model behavior with respect to observed mean transports and its variability. Thus, earlier studies validated the model and showed that FLAME is suitable for applications in the tropical North Atlantic.…”
Section: The Flame Modelmentioning
confidence: 99%
“…[12] The bathymetry in FLAME lacks some detail in the area of complex topography, such as the Lesser Antilles passages (e.g., missing some of the deep parts, see Kirchner et al [2008] for details). The Lesser Antilles are represented as shallow ocean points and are still about 35 m deep.…”
Section: The Flame Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1), connecting the Caribbean See with the Atlantic. Recent observation and model study suggest that a total flow of 17-19 Sv 30 passes through the Lesser Antilles into the Caribbean Sea (Kirchner et al, 2008), implying that the western boundary current across the 14.5° N section must recirculate southward across the section in the east, as occurs in both realizations (Fig. 12a, b).…”
Section: Conclusion 30mentioning
confidence: 80%